A 3‐D shear wave velocity model for Myanmar region - Oo, Kyaw Moe (2019)
Myanmar is located at the eastern margin of the ongoing Indo‐Eurasian collision system, has experienced a complex tectonic history and is threatened by a high level of seismic hazard. Here we develop a crustal scale 3‐D seismic velocity model of Myanmar, which is not only critical for understanding the regional tectonic setting and its evolution but can also provide the foundation for a variety of seismological studies, including earthquake location determinations, earthquake focal mechanism inversions, and ground motion simulations. We use the newly deployed Earth Observatory of Singapore‐Myanmar broadband seismic network and other seismic stations in and around Myanmar to study the station‐based 1‐D velocity structure through a joint inversion of receiver functions, H/V amplitude ratio of Rayleigh waves, and surface wave dispersion measurements. Our results reveal a highly variable crustal structure across Myanmar region, characterized by a series of N‐S trending sedimentary basins, with thicknesses up to ~15 km in central Myanmar and an ~5‐km step in the depth of the Moho across the Sagaing‐Shan Scarp fault system. We interpolate our station‐based 1‐D velocity profiles to obtain an integrated 3‐D velocity model from southern Bangladesh to Myanmar. Using three regional earthquakes located to the south, within, and north of the seismic network, we show that our proposed model performs systematically better than the CRUST 1.0 model for both Pnl waves and surface waves. Our study provides a preliminary community velocity model for the region, with further refinements and interpretations anticipated in the near future.